Values education through history : peace & tolerance - Quisumbing, Lourdes R. ; Sta. Maria, Felice P. (Pasay City, Philippines : UNESCO National Commission of the Philippines, 1996)
As we face the twenty-first century and the new millennium with raised hopes of economic development for our country and a better life for our people, the dream of peace in our land and in the rest of the world cries out for attention as well. We need to foster a culture of peace, peace that upholds not simply the absence of war but also economic and social justice, human rights and fundamental freedoms, and sustainable development.
Part I. Values education towards a culture of peace -- Part II. Proceeding of communicating history.
Includes bibliographical references and index.
Keywords: MORAL EDUCATION